2018
DOI: 10.5858/arpa.2018-0244-oa
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Squamous Cells of Undetermined Significance Cervical Cytology Report Rate and Histologic Follow-up Findings From the Largest College of American Pathologists–Certified Laboratory in China

Abstract: Context.— Reports for atypical squamous cells of undetermined significance (ASC-US) and histologic findings are rare in China. Objective.— To analyze the correlation findings of ASC-US cytology with high-risk human papillomavirus (hrHPV) test and histopathologic follow-ups. Design.— ASC-US cases with hrHPV test and histologic follow-ups between 2011 and 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 26 publications
5
19
1
3
Order By: Relevance
“…Pooled hrHPV testing has been used routinely worldwide to stratify risk in women with ASC‐US cytology. Previous studies have shown that CIN2+ lesions are found in approximately 5%‐21.2% of women with ASC‐US/hrHPV+, though these findings are based predominantly on results obtained using the HC2 platform 15‐20,24 . Our results show that detection rates of CIN2+ lesions in women with ASC‐US/hrHPV+ using the hrHPV testing platforms HC2, Cervista, and Aptima are low (<10%) and that most women with ASC‐US/hrHPV+ do not harbor a high‐grade cervical lesion on immediate histologic follow‐up.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Pooled hrHPV testing has been used routinely worldwide to stratify risk in women with ASC‐US cytology. Previous studies have shown that CIN2+ lesions are found in approximately 5%‐21.2% of women with ASC‐US/hrHPV+, though these findings are based predominantly on results obtained using the HC2 platform 15‐20,24 . Our results show that detection rates of CIN2+ lesions in women with ASC‐US/hrHPV+ using the hrHPV testing platforms HC2, Cervista, and Aptima are low (<10%) and that most women with ASC‐US/hrHPV+ do not harbor a high‐grade cervical lesion on immediate histologic follow‐up.…”
Section: Discussioncontrasting
confidence: 49%
“…Recent studies have found a high prevalence of CIN2/3 in women aged 21‐24 years with ASC‐US cytology and have suggested that it may be prudent to consider alternative surveillance, such as colposcopy, in similar high‐risk populations 32,33 . In addition, a large‐scale study of ASC‐US in the Chinese population showed that the rate of hrHPV positivity decreased with increasing age and was highest in women aged <20 years 20 . In the present study, our results show that the immediate histologic correlation rates in the younger population were lower than those in older populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by a population-based the study in Chinese population, ASC-US PPV was roughly 5% -17% [5] . Accordingly, ASC-US PPV in present study were 6.28% in CIN2+, 19.97% in CIN1 and 0.57% in squamous cell carcinoma, similar to 6.5% (29/446) CIN2+ detection rate by Lopez-Alegria F et al [22] .…”
Section: Diagnostic Yield and Performance Of Cervical Cancer Screeningmentioning
confidence: 89%
“…According to the most recent Surveillance, Epidemiology, and End Results (SEER) data from 2012-2016, the incidence rate for cervical cancer had declined to 7.3/100,000 per year in the United States in contrast to 15.6/100,000 per year in China. Despite Ivyspring International Publisher of local efforts and international assistance to scale up effective cervical cancer prevention service [3][4][5] , about 80% cervical cancer burden from source-poor regions remains as a nationwide health issue [6][7][8] . Latest cervical cancer statistical studies have shown that more than 85% of cervical cancer patient in Shanxi Province had never received proper screening and presented at late stage.…”
Section: Introductionmentioning
confidence: 99%